SURVEI AWAL KEANEKARAGAMAN ORDO ANURA DI DESA KETENGER, BATU RADEN, JAWA TENGAH - Ratna P, I.G.A Ayu; Wijaya, E.A.P Willy (Indonesian Journal of Conservation, 2013)
Ketenger, Batu Raden is located on the southern slope of Mount Slamet, Central Java. The Anuranâs biodiversity in this area is assumed to be high since Ketenger is relatively undisturbed and has many locations that suitable as Anuranâs habitast.The aim of this research was to study kind of anurans in Ketenger, Batu Raden, as the preliminary data for the further research. The survey was conducted on June â July 2013, using Visual Encounter Survey (VES) method. Thirtheen anurans, from five families, were recorded during the survey. They were Leptobrachium hasseltii, Microhyla achatina, Limnonectes kuhlii, Limnonectes microdiscus, Fejervarya limnocharis, Rana chalconota, Rana hosii, Huia masonii, Rhacoporus reinwardtii, Polypedates leucomystax, Philautus aurifasciatus, Phrynoidis aspera dan Duttaphrynus melanosticus. Three species, Huia masonii, Limnonectes kuhlii and Microhyla achatina,were known as endemic species of Java.Â Desa Ketenger, Batu Raden terletak di sebelah selatan kaki Gunung Slamet, Jawa Tengah. Daerah ini memiliki wilayah hutan yang relatif masih alami dan beberapa wilayah yang sesuai dengan habitat Anura, sehingga diduga keanekaragaman Anura di daerah ini tinggi. Penelitian ini bertujuan untuk mengetahui jenis-jenis Anura di Desa Ketenger, Batu Raden, sebagai data awal untuk penelitian selanjutnya. Survei dilakukan pada bulan Juni â Juli 2013 dengan menggunakan metode Visual Encounter Survey (VES). Total ditemukan 13 spesies anggota ordo Anura, yang termasuk dalam 5 famili. Jenis-jenis Anura tersebut antara lain: Leptobrachium hasseltii, Microhyla achatina, Limnonectes kuhlii, Limnonectes microdiscus, Fejervarya limnocharis, Rana chalconota, Rana hosii, Huia masonii, Rhacoporus reinwardtii, Polypedates leucomystax, Philautus aurifasciatus, Phrynoidis aspera dan Duttaphrynus melanosticus. Tiga jenis Anura, yaitu Huia masonii, Limnonectes kuhlii dan Microhyla achatina merupakan spesies endemik Jawa.Â